The Existence of Parents and Islamic Religious Education Teachers in Instilling Worship Awareness Among Students at Rumah Tahfidz Al Wasathiyyah Tanrutedong - Nur Ardiansyah; Raya Mangsi; Suredah Hamid (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study is motivated by the significant role of parents and Islamic Religious Education (PAI) teachers in fostering worship awareness among the students of Rumah Tahfidz Al Wasathiyyah Tanrutedong. The research questions are: 1) How is the existence of parents and PAI teachers in this process? 2) What forms of cooperation exist between them? and 3) How is the level of worship awareness among the students at Rumah Tahfidz Al Wasathiyyah? The purpose of this study is to describe the existence of parents and PAI teachers in instilling worship awareness in the students of Rumah Tahfidz Al Wasathiyyah Tanrutedong, to identify the forms of cooperation between parents and teachers in this process, and to analyze the level of worship awareness possessed by the students as a result of the interaction and guidance provided by both parties. To achieve these objectives, this research employs a qualitative approach with data collected through observation, in-depth interviews, and documentation, which are then analyzed using content analysis techniques. The findings of this study indicate that parents play an essential role in instilling worship awareness in their children through prayer, advice, exemplary behavior, guidance, and supervision. Meanwhile, Islamic Religious Education (PAI) teachers demonstrate their role as advisors, role models, companions, supervisors, evaluators, and motivators. Worship awareness among students at Rumah Tahfidz Al Wasathiyyah Tanrutedong is also fostered through a structured and continuous collaboration between parents and PAI teachers, which includes effective communication, enhancement of parents’ religious understanding, mutual agreements on rewards and punishments, relational support from parents to teachers, and reinforcement within the family environment. This synergy contributes to the development of students’ worship awareness based on three key indicators: (1) Obedience in performing obligatory and recommended (sunnah) acts of worship (1) Independence in maintaining regular worship practices without strict supervision, and (3) The emergence of a culture of mutual reminders among students regarding worship